STRATEGI PENGEMBANGAN WISATA PANTAI DI KAWASAN PULAU TIGA NEGERI URENG-ASILULU KABUPATEN MALUKU TENGAH (PENDEKATAN ANALISIS KESESUAIAN DAN DAYA DUKUNG) - Renoldy L. Papilaya; Selviana Tanalessy (Universitas Pattimura, 2022)
This study aims to analyze the suitability of tourism in the Tiga Island clusters, analyzing the carrying capacity of the tourist areas of Tiga Island clusters and the development strategy of the tourism area of Tiga Island clusters. The data sources used in this study are primary data and secondary data while analyzing data using land suitability criteria for coastal tourism and the carrying capacity of the tourist areas (Yulianda, 2007). To produce a strategy of development of the tourism area of Tiga Island clusters using SWOT methods and TOWS (Rangkuti, 2005). The results showed that the tourist area of Ela Island on station 1 is very suitable; station 2 is quite appropriate, stations 3 and 4 are conditional to conduct tourist activities of the beach recreation category. The tourist area of Hatala Island on stations 1 and 2 are quite appropriate, stations 3 and 4 are conditional. The tourist area of Lain Island on station 1 is quite appropriate, 2, 3 and stations 4 are conditional. The tourist area of Ela Island with an area of 39,530 m2 can accommodate 1,395 tourists/day, tourism area of Hatala Island with an area of 55,206 m2 can accommodate the 2.143 of tourists/day, and the tourism area of other islands with an area of 12,069 m2 can only accommodate 406 tourists/day. As a result, 11 strategies and 23 directions are formulated for the development of the tourist areas of Ela Island, Hatala Island and Lain Island.